Asymmetric Dimethylarginine Protects Neurons from Oxygen Glucose Deprivation Insult by Modulating Connexin-36 Expression. (6th July 2022) - Fang, Kun; Chen, Shufen; Wang, Yi; Chen, Fangzhe; Cui, Mei; Dong, Qiang
Abstract : Background . Asymmetric dimethylarginine (ADMA) is a nonselective nitric oxide synthase inhibitor. ADMA is thought to inhibit the production of nitric oxide (NO) by neurons after oxygen-glucose deprivation (OGD). The gap junction protein Connexin-36 (cx-36) is involved in the pathophysiology of stroke. We investigated whether ADMA could protect neurons from OGD insults by regulating the expression of cx-36. Methods . Cultured rat cortical neuronal cells were used. Neurons were treated with OGD with or without ADMA pretreatment. The lactate dehydrogenase (LDH) release rate was used to assess neuronal injury. Intracellular NO levels were determined using 4-amino-5-methylamino-2 ′, 7 ′ -difluorofluorescein diacetate. Western blotting was performed to detect cx-36 expression. Results . The LDH release rate increased in the supernatant of neurons after the OGD insult, whereas ADMA treatment reduced the LDH release rate. Intracellular NO levels increased following OGD treatment, and this increase was not inhibited by ADMA treatment. Expression of cx-36 was upregulated in neurons under OGD conditions, and treatment with ADMA downregulated the expression of cx-36. Conclusions . ADMA protects neurons from OGD insult, and cx-36 downregulation may be a possible pathway involved in ADMA-mediated neuronal protection.